Uma vida dominada pela dor: a criança vivenciando a Anemia falciforme - Souza, Ana Augusta Maciel de [UNIFESP] (2011)
Sickle-cell anemia is characterized by chronic hemolytic anemia caused by anomalous red blood cells, HbS. Its complications result in painful crises as a result of vasoclusive episodes that affect several organs and articulations and that can lead to infections thus causing deep suffering for the child and his/her family. The present study, a qualitative research project, aimed to understand the meaning the child attributes to having sickle-cell anemia. The Symbolic Interactionism was used as the theoretical framework and the Grounded Theory, as the methodological one. Subjects were eight children whose age ranged from 4 to 10 years old and the strategies used for data collection were: observant participation, interviews with the child mediated by the use of the Therapeutic Play and semi-structured interviews with their parents, as informants of the child’s experience. Data comparative analysis allowed the identification of A life dominated by pain as the conceptual category and revealed that having sickle-cell anemia is a very painful experience for the child. Data also showed that pain is the heaviest burden the child experiences and makes him/her very sad due to the constant interaction with a painful body requiring continuous care, drugs, hospital admissions and outpatient care. Such interventions expose the child to equally painful, invasive and stressing procedures that the child himself/herself recognizes as necessary to relieve pain. Moreover, the category also reveals that the child suffers for having to deal the family stigma related to the illness and for being aware that the treatment is just palliative care and that a relapse may occur at any time. To face suffering, the child feels the mother is a “safe harbor”, relies on faith, tries to be strong and hopes that the definitive cure for sickle-cell anemia will be achieved. Results emphasize the importance of providing support to the family so that they can help the child cope with this illness. The systematic use of the Therapeutic Play to plan nursing interventions aimed at this population of children is equally important.